Effects of charges on the particle motion above fluidized beds - Raszillier, Hans; Mohr, Bernhard; Durst, Franz (International Journal of Multiphase Flow, 1990)
The paper is concerned with the effects of electric charges on the motion of metallically coated particles in fluidized beds. It treats a particular kind of collision process between such particles, which happens on the upper layers of such a bed. Photographic studies are provided displaying the phenomenon. In order to explain it, the interaction of a pair of spherical charged particles surrounded by a dielectric fluid is analyzed theoretically. It is shown that the peculiarities of the collision are related to the fact that two conducting particles of the same diameter, even if they have charges of the same sign, but of different magnitude, attract each other when they approach close enough and that they repel after collision because of the charge redistribution between them. It turns out that the experimental observations are well-described by this theoretical picture.
Keywords: electric charge; fluidized bed; particle collision